Kelayakan Pengembangan Bisnis E-Marketplace Perjalanan Ibadah Umrah Pada PT. Sarana Transwisata Teknologi - Oktoyadi Oktoyadi; Sri Wahyuni (Sekolah Pascasarjana Perbanas Jakarta, 2019)
The purpose of this fnal project is to analyze and find out the business feasibility of umra travelling e-marketplace development by PT Sarana Transwisata Teknologi, viewed from market and marketing aspect and environmental aspect. The problems that arise in the implementation of umrah worship trips in Indonesia have encouraged PT Sarana Transwisata Teknologi to provide the e-marketplace that offers quaranteed umrah pilgrimage products. Using the concept of strategic management and competitive advantage, this final project analyzes the feasibility of developing the iGoUmroh e-marketplace business in the Umrah pilgrimage industry. Based on observations and interviews with actors in the Umrah travel industry, iGoUmroh e-marketplace has a competitive advantage over its competitors in the form of guarantees from the official guarantor institution for the products offered in e-marketplace. However, iGoUmroh must always innovate to be able to create new competitive advantages in order to survive and lead in the industry for organizing umrah pilgrimages